Role of Sonoelastography in Evaluation of Lymph Node Metastasis in Head and Neck Keeping Histopathology as Gold Standard - Javed, Maaza; Sarfraz, Saulat; Naseem, Nawal; Javed, Abdullah; Javed, Saadullah; Mahmood, Hafiz Abad (Indus Journal of Bioscience Research, 2025)
Objective: To determine the diagnostic accuracy of sonoelastography in the evaluation of lymph node metastasis in head and neck cancer, using histopathology as the gold standard. Research Design: A study of cross-sectional validation. Duration and Place of Study: This research was carried out in the Diagnostic Radiology Department, Shaikh Zayed Hospital, Lahore, from May 2024 to November 2024. Methodology: A total of 138 patients aged 18 to 70 years, with enlarged cervical lymph nodes (≥1 cm), were included. Participants were evaluated using sonoelastography, a high-resolution ultrasound-based technique, performed by an experienced radiologist. Elastographic tissue stiffness was scored from 1 to 4, with scores 1 and 2 indicating benign nodes and scores 3 and 4 indicating malignancy. The reference standard for biopsy sample analysis was histopathological analysis. The following metrics were computed: diagnostic accuracy, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). Results: The mean age of participants was 55.19 ± 5.67 years, with a mean lymph node size of 2.16 ± 0.22 cm. Sonoelastography identified 38.4% of lymph nodes as malignant and 61.6% as benign, compared to histopathological findings of 30.4% malignant and 69.6% benign. Diagnostic performance metrics for sonoelastography included sensitivity of 86%, specificity of 82%, PPV of 68%, NPV of 93%, and an overall diagnostic accuracy of 83%. Conclusion: Sonoelastography demonstrates high sensitivity and diagnostic accuracy in evaluating cervical lymph nodes, making it a valuable, non-invasive adjunct to conventional imaging methods.